Association between abdominal obesity and demographic factors according to altitude levels in Peru - Pajuelo Ramírez, Jaime (2020)
Objective. To determine in the adult population of Peru, the characteristics of abdominal obesity and its relationship with different levels of geographic altitude, according to gender, age groups, nutritional status, and area of residence. Methods. A descriptive study was carried out based on secondary sources: National Household Survey (ENAHO 2012-2013) of the National Institute of Statistics and Informatics (INEI) and Ministry of Health Lima, Peru. Abdominal obesity was identified by waist circumference and waist / height ratio. The altitude was stratified into 3 levels: <1000 meters above sea level, from 1000 to 2999 meters above sea level, and ≥ 3000 m.a.s.l. Results. The highest prevalence of abdominal obesity was found in the female gender (48,2% - 87,4%), in the age group from 40 to 59 years (38,4% - 89,5%), in the obese (85,9% - 99,9%), and in urban areas (36,8% - 86,3%), respectively. These prevalences decreased from 1000 meters above sea level, with the exception of those corresponding to nutritional status. The prevalence ratio adjusted for gender, age group and area of residence, showed a decrease in relation to altitude. Conclusion. The population living in high-altitude cities showed low prevalence of abdominal obesity in relation to those living in lower-altitude cities.